Cattle theft and recovery challenges along South Africa’s borders: A case study of North-West Province - Matshego, Joseph Nkashe; Gololo, Sechene Stanley; Sesale, Eunice Lebogang; Seeletse, Solly Matshonisa (Journal of Cultural Analysis and Social Change, 2025)
Livestock theft, particularly cattle, has emerged as a persistent issue along the borders of South Africa, undermining agricultural productivity, economic stability, and the livelihoods of rural communities. Despite the implementation of various legal frameworks aimed at mitigating theft and aiding the recovery of stolen livestock, significant challenges persist, especially with the facilitation of cross-border movement by thieves and stolen cattle. This manuscript explores the systemic barriers to effective cattle recovery. It focuses on the role of livestock passports, and provides an in-depth case study of North-West Province, where theft is particularly rampant. We examine the dynamics of livestock theft, the legal and logistical hurdles in recovering stolen cattle, and the socio-economic impacts on the affected communities. Key recommendations are proposed to strengthen security mechanisms and improve the effectiveness of recovery systems.